Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1986
DOI: 10.1007/bf00541283
|View full text |Cite
|
Sign up to set email alerts
|

Granulocyte elastase as a new biochemical marker in the diagnosis of chronic joint diseases

Abstract: Human granulocyte elastase (EC 3.4.21.37) is released from granulocytes in large amounts in chronic inflammatory joint diseases and is therefore of special pathogenic and diagnostic importance. In order to examine the diagnostic significance of this enzyme as a clinico-chemical parameter, we determined the concentration of granulocyte elastase in complex with alpha 1-proteinase inhibitor by an enzyme immunoassay in synovial fluids and plasma of patients with chronic joint diseases. In inflammatory synovial flu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
5

Year Published

1987
1987
2020
2020

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 37 publications
(22 citation statements)
references
References 52 publications
1
16
0
5
Order By: Relevance
“…The level of EIC in the plasma of patients with RA was shown to be significantly higher than that in the plasma of healthy controls (P<0.01) as previously reported [32][33][34][35]. Furthermore, the level of EIC in the patients with MRA was significantly higher than that in patients with RA (P<0.05; Table 1).…”
Section: Discussionsupporting
confidence: 70%
“…The level of EIC in the plasma of patients with RA was shown to be significantly higher than that in the plasma of healthy controls (P<0.01) as previously reported [32][33][34][35]. Furthermore, the level of EIC in the patients with MRA was significantly higher than that in patients with RA (P<0.05; Table 1).…”
Section: Discussionsupporting
confidence: 70%
“…Together with elastase—a proteolytic enzyme stored in the azurophil granules—high concentrations of lactoferrin are evident in affected joints,40 41 and raised circulating levels have been shown in RA 42. Strong correlations with elastase-proteinase inhibitor complex and C reactive protein measurements of disease activity have advanced lactoferrin as a possible marker for neutrophil dependent inflammation in RA.…”
Section: Discussionmentioning
confidence: 99%
“…Alternatively, neutrophilic proteinases leaking from the joints may also have contributed to intravascular consumption of a2M. Elevated plasma levels of elastase-a,AT in RA have been reported in several studies (54)(55)(56)(57), and it has been suggested that this measurement would be useful in differentiating between RA and OA (57). Our findings support this notion: Plasma levels of elastase-a, AT were significantly increased in patients with RA, as compared with the levels in patients with OA and in normal controls (Table 3).…”
Section: Discussionmentioning
confidence: 99%